Environmental Toxicants as Extrinsic Epigenetic Factors for Parkinsonism: Studies Employing Transgenic C. elegans Model - Jadiya, Pooja; Nazir, Aamir (CNS & Neurological Disorders - Drug Targets, 2012)
Various human diseases are known to occur as a result of gene-environment interactions. Amongst such diseases, neurodegenerative Parkinson's disease (PD) is a complex disorder in which genetics and exposure to toxins constitute the main determinants in the onset of the disease. Many studies have reported on a link between pesticide exposure and increased risk of PD, however the role of different classes of pesticides vis-a-vis Parkinsonism has not been well elucidated. We carried out the present study to explore the role of six groups of pesticides viz botanicals, herbicides, fungicides, organophosphates, carbamates and pyrethroids on PD and and associated neurotoxic effects. These pesticides were studied using transgenic Caenorhabditis elegans model expressing human alpha synuclein protein tagged with yellow fluorescent protein [NL5901; (Punc-54::alphasynuclein::YFP+unc-119)] in the body wall muscle. Amongst all the classes of pesticides examined, botanical rotenone showed severe effects on PD pathogenesis. It significantly increased alpha synuclein aggregation and oxidative stress. Furthermore, it reduced mitochondrial and lipid content in the worms. Pesticides from other classes were observed to exert marginal effects as compared to rotenone thus suggesting that there is a class or structure specific effect of environmental chemicals vis-a-vis Parkinsonism. Hence it may be deduced that all classes of toxicants do not induce similar effects on neurodegeneration and associated events.
Keywords: Caenorhabditis elegans